The Effects of Positive Allosteric Modulators of α7-nAChR on Social Play Behavior in Adolescent Rats Prenatally Exposed to Valproic Acid - Kinga Gzielo; Agnieszka Nikiforuk (MDPI AG, 2022)
There is still no effective treatment that addresses the core symptoms of autism spectrum disorders (ASD), including social and communication deficits. A comprehensive body of evidence points to the cholinergic system, including alpha7-nicotinic acetylcholine receptors (α7-nAChRs), as a potential target of pharmacotherapy. A promising approach is based on positive allosteric modulators (PAMs) of these receptors due to their advantages over direct agonists. Nevertheless, α7 n-AChR ligands have not been widely studied in the context of autism. Therefore, using one of the most widely used rodent models of ASD, that is, prenatal exposure to valproic acid (VPA), we examined the impact of α7-nAChR PAMs (PNU-120596 and CCMI) on socio-communicative behavior during social play in adolescent male and female rats. The current study demonstrated that PAM treatment affected certain aspects of socio-communicative behavior in adolescent rats. Accordingly, PNU-120596 ameliorated deficient play abilities in VPA-exposed males, as revealed by increased play time during a social encounter. In addition, this compound enhanced the emission of ultrasonic vocalizations that accompanied playful interactions. Moreover, we observed the overall effect of PNU-120596 on non-playful forms of social behavior (i.e., social exploration) and acoustic parameters (i.e., the duration) of emitted calls. The present results suggest the ability of α7-nAChR PAMs to facilitate socio-communicative behavior in adolescent rats.